Die deutsche geographische Japan-Forschung vor und nach der Meiji-Restauration - Troll, Carl (ERDKUNDE, 1968)
The Meiji restoration of 1868, the centenary of which occours in Japan this year, was not only a fundamental caesura in the political, cultural, economic and social history of the country, but also in the history of its scientific study. Geography is at the same time remembering the 50th anniversary of the death of J. J. Rein who, after the opening of the country in 1868, was the first geographer to journey there and carry out systematic research. In addition, 1966 saw the 100th anniversary of the death of Ph. F. von Siebold and the 250th anniversary of the death of Engelbert Kaempfer, the German doctors and natural scientists. In Shogunat times, these two, based in the Dutch trade mission at Dashima-Nagasaki began, under conditions of personal danger, the first investigations into ’forbidden’ Japan. An appreciation of these three classical researchers of Japan is accompanied by a short review of German research into Japan since J. J. Rein, culminating in the new book by Martin Schwind. Contemporary research into the population, settlement, economic and social geography of Japan is centrally concerned with the relationships between the Western-style technological civilisation and the traditional culture of the Japanese themselves. (P. Schöller